Perception of Learning Management System Among Distance Learners in South-West, Nigeria - Esther M. Ajijola; Oyeronke Olufunmilola Ogunlade; Gboyega Ayodeji Aladesusi; Charles O. Olumorin (MO.RI Publishing, 2021)
Learning Management System (LMS) is a common platform where students and teachers can interact digitally, most especially in Open and Distance Learning (ODL) institutions. However, it has been discovered over time that most of the distance learners with poor study habits lag behind in its utilization. The purpose of this study was to investigate the Perception of Learning Management System among Distance Learners’ in South-West, Nigeria. Emphasis was on gender and field of study using an adapted Technology Acceptance Model (TAM). This study employed a descriptive research method. Data were collected through the administration of a-validated researcher-adapted questionnaire. Descriptive statistics of mean and standard deviation were used to answer research questions one and two. Inferential statistics of t-test and ANOVA were used to test the hypotheses at 0.05 level of significance. The research findings indicated that there were significant differences between male and female distance learners in their: perceived usefulness of LMS (p=0.00); perceived ease of use of LMS (p=0.004); in favour of males; there was no significant difference among Sciences, Arts and Social Science distance learners on their perceived usefulness and perceived ease of use of LMS. It was therefore recommended that training and support programs be established to ensure a sustainable use and prevent collapse of LMS in the institutions in respective of distance learners’ gender and field of study.